Design and Implementation of an Electronic Constant Current DC Load for Battery Discharge and Power Supply Test Systems - Ceylan, Murat; Balıkçı, Abdulkadir (IEEE, 2014)
Constant current load devices are necessary for test systems whose purpose is to characterize battery discharge behaviour properly, since the voltage, and thus the current of a battery decreases as it is discharged if a constant resistance load is used. In this work, an electronic constant current DC load was designed and implemented. The main topology is based on a voltage follower controlling the gate voltage of a MOSFET that operates in linear mode. The implemented circuit can also be used in order to test the reliability of power supplies under different loading conditions. The results of different test scenarios are presented.
16th International Power Electronics and Motion Control Conference and Exposition (PEMC) -- SEP 21-24, 2014 -- Antalya, TURKEY
Keywords: constant current; electronic load; battery; power supply; MOSFET; linear mode